Strategi Komunikasi Biro Perjalanan Umrah dalam Membangun Kepercayaan Jamaah Melalui Media Digital: Studi Kasus Arrahmah Tour - Sriyono Sriyono; Mohammad Ridwan; Sukamto Sukamto; Sulistyo Suharto (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze the digital communication strategy of Arrahmah Tour in building pilgrims’ trust through digital media. This research employs a qualitative approach with a case study method. Data were collected through interviews, observation of the company’s official digital media, particularly the website Arrahmah Tour, and documentation of various digital contents such as company profiles, travel packages, pilgrims’ testimonials, and service information. Data analysis was conducted using a descriptive-qualitative technique focusing on identifying patterns of digital communication strategies in building trust. The findings show that Arrahmah Tour implements a digital communication strategy focused on building digital trust through three main elements: information transparency, social proof, and communication consistency. Digital media functions not only as a promotional tool but also as an organizational legitimacy instrument and a mechanism for reducing perceived risk among prospective pilgrims. The company’s website serves as an information hub as well as a primary reference in the decision-making process. Thus, the implemented digital communication strategy significantly contributes to building pilgrims’ trust in the context of high uncertainty within the Umrah travel industry.